Christian Summer Camp Ástjörn in Iceland in the experiences of children - Magdalena Agnieszka Palec; Teresa Parczewska (Journal of Modern Science)
The aim of the research project was to present a phenomenon of the Ástjörn Christian summer camp in Iceland from the perspective of the campers. The research used qualitative methods (semi-structured interviews and a document analyses). A content analysis technique was used to interpret the data. A total of 190 children (participants in the Ástjörn Christian Summer Camp in Iceland) aged 6 to 12 were surveyed. In order to find out the campers' opinions, they were asked three open questions that addressed: (1) favorite places and activities; (2) motives for coming to camp; and (3) peculiarities of the camp. The study presents the main findings of the study detailing the emergent model of the Ástjörn Christian camps with six basic features: relationality, separation from home, care and safety, focus on faith, freedom, and connection to nature. The data analyzes carried out proved that among the important features determining the attractiveness and uniqueness of Camp Ástjörn, it is determined not only by its location and the beauty of the landscape, but above all by its interesting program, its participants and relationships.